An Efficient Intrusion Detection System Using Improved Bias Based Convolutional Neural Network Classifier (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today’s modern society has faced many challenges due to the rapid digitization and growing number of hackers, which makes the networking-based systems to become a target place for intruders. The attacks may allure the users, and it compromised the whole system and makes the security the biggest challenge. In this regard, the best way to combat the issues is by exploring new ways to defend the network against threats. More recently, Intrusion Detection Systems (IDS) is a key enabling technology in maintaining the novel network security. Indeed, some existing systems utilize Improved Relevance Vector Machine (IVRM) classifier for performing intrusion detection in network-based systems.  In this work, feature selection is done by using Gaussian Firefly Algorithm and Improved Relevance Vector Machine (IRVM) based classification is performed according to the selected features. However, for large-scale intrusion dataset, the intrusion detection is not robust; hence, it leads to high attack rates. The proposed system designed an Improved Bias based Convolutional Neural Network (ICNN) for high attack intrusion detection.  For embracing high-security factors and enhanced protection, the proposed system performs three phases, such as preprocessing, feature selection, and classification. The first phase employs the KDD dataset and Kalman filtering method followed by feature selection utilizes Inertia Weight based Dragonfly Algorithm (IWDA) and finally identified the intrusion attacks using Improved Bias based Convolutional Neural Network (IBCNN) classifier. In this work, a novel model performed with the KDD dataset. The suggested method evaluated in terms of accuracy, f-measure, recall, and precision for examining performance compared with existing systems.